Pengaruh Metode Secara Variatif Dalam Mata Pelajaran Akidah Akhlak Terhadap Nilai Berkeadaban (Ta’addub) Peserta Didik Fase D - Salamudin, Ceceng; Maulani, Nisa Fitri (STAI Al-Musaddadiyah Garut, 2025)
Learning Moral Creeds in madrasas is one of the important subjects to instill a positive influence on the application of morals in madrasas. One of the causes of students' lack of understanding of moral values ​​is the lack of variation in learning methods. The current problem of globalization makes it difficult for children to apply good morals, whether morals towards Allah, morals towards others and morals towards nature. This research aims to describe the influence of varied methods in the Aqidah Akhlak subject on the civilized values ​​(Ta'addub) of Phase D students at MTs Al-Musaddadiyah Garut. The method used in this research is descriptive with an inferential quantitative approach, so that a relationship is obtained between the Independent Variable (Variative Method) and the Dependent Variable (Civilized Values ​​(Ta'addub)). The subjects of this research were Phase D students at MTs. Al-Musaddadiyah Garut, namely 32 people. Based on statistical tests, there is an influence of varied methods on the formation of Civilized Values ​​(Ta'addub) of 87%, while other factors that influence students' Civilized Values ​​(Ta'addub) are 13% but were not examined in this research. Keywords: Varied methods, students' civilized values ​​(ta'addub).